Application of compound lidocaine cream for preemptive analgesia in placement of stereotactic head frames for Gamma Knife treatment (复方利多卡因乳膏超前镇痛在伽玛刀治疗固定立体定位头架中的应用) - WU XunXin (吴逊欣); LI Dongna (李冬娜); ZENG Dongyu (曾冬玉) (中西医结合护理)
Objective To compare the pain and stress reaction of patients with topical anesthesia using local lidocaine injection and topical anesthesia using local lidocaine injection combined with compound lidocaine cream in advance in the placement of stereotactic head frames for Gamma Knife treatment. Methods Totally 438 patients were randomly divided into experimental group (n = 219) and control group (n = 219). In the experimental group, 5% compound lidocaine cream was applied at the two points behind the forehead pillow 1 hour before placement of skull fixed stereotactic head frames, and then the stereotactic head frame was installed after local drug infiltration and local anesthesia with lidocaine injection. In the control group, the stereotactic head frame was placed after topical anesthesia using local lidocaine injection. Visual analogue scale (VAS) score was used for pain self-assessment, and Faces Pain Scale Revised (FPS-R) was used to objectively determine the degree of facial expression pain. The pain score and grading were performed before, during and after fixation, and the changes of mean arterial pressure and heart rate before and after the placement of head frames under stress. Results There was no significant difference in VAS score, FPS-R grade, mean arterial pressure and heart rate between the two groups before fixation (P>0. 05), while the VAS score of the experimental group and the control group decreased significantly during fixation (P <0. 0001). The FPS-R pain grade of the experimental group was higher than that of the control group (P < 0. 001), and the VAS score of the experimental group was lower than that of the control group 5 minutes after fixation (P < 0. 0001). The FPS-R pain grade of the experimental group was more painless than that of the control group (P < 0. 001). The mean arterial pressure measured immediately after fixation in the experimental group was lower than that in the control group (P < 0. 001), and the heart rate measured immediately after fixation in the experimental group was lower than that in the control group (P < 0. 05). Conclusion Applying 5% compound lidocaine cream to the nail position before stereotactic head frame fixation for Gamma Knife treatment can produce good preemptive analgesic effect, reduce the risk of syncope and epilepsy caused by pain during head frame installation, and increase the comfort in the treatment process. (目的 比较提前使用复方利多卡因乳膏涂抹表皮麻醉后再联合利多卡因局部麻醉与单用利多卡因注射液局部麻醉, 应用于伽玛刀治疗固定立体定位头架过程中患者的疼痛及应激反应。方法 选取暨南大学附属第一医院伽玛刀中心2020年7月—12月收治患者438 例, 随机分为研究组(n= 219)和对照组(n= 219)。研究组采用头部固定立体定位头架前1 h在额头枕后各两点钉位处涂抹5%复方利多卡因乳膏, 待局部药物浸润后行利多卡因局部麻醉后再安装立体定位头架; 对照组常规采用利多卡因注射液局部麻醉后再安装立体定位头架。自我评估法采用视觉模拟评分法(VAS)评分, 行为评估法采用修订版面部表情疼痛量表(FPS-R), 对患者面部表情疼痛程度进行客观判定, 并在固定前、固定中、固定后进行疼痛评分及分级。记录患者应激状态下安装头架前、后时平均动脉压与心率变化。结果 两组患者行伽玛刀固定立体定位头架在固定前VAS评分、FPS-R分级、平均动脉压及心率比较, 差异无统计学意义(P>0. 05)。固定过程中, 研究组与对照组的VAS评分明显降低, 差异有统计学意义(P<0. 0001); 研究组的FPS-R疼痛分级轻痛多于对照组, 差异有统计学意义(P<0. 001)。固定后5 min研究组的VAS评分低于对照组, 差异有统计学意义(P<0. 0001); 研究组的FPS-R疼痛分级无痛多于对照组, 差异有统计学意义(P<0. 001)。固定后研究组立即测得平均动脉压低于对照组, 差异有统计学意义(P<0. 001); 固定后研究组立即测得心率低于对照组, 差异有统计学意义(P<0. 05)。结论 伽玛刀治疗固定立体定位头架前给予5%复方利多卡因乳膏涂抹钉位处可产生良好的超前镇痛效果, 对于降低头架安装过程中因疼痛产生的晕厥、癫痫等发生具有积极意义, 能够增加治疗过程中的舒适度。)